Handbook of hyper-real religions - Possamai, Adam. (Leiden : BRILL, 2012)
'Hyper-real religions' are innovative religions and spirituality that mix elements of religious tradition with popular culture. Through various case studies, this book studies the on and off-line religious/spiritual consumption of these narratives through a social scientific approach.
Fantasy, Conspiracy and the Romantic Legacy: Max Weber and the Spirit of Contemporary Popular CultureConclusion: The Future of Hyper-Real Religions?; Contributors' Biographies; Index.
Description based on print version record.
Keywords: Religion and culture; Popular culture -- Religious aspects; RELIGION / History; TRAVEL / Special Interest / Religious; Electronic books